2023
DOI: 10.3390/jpm13030475
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Peripheral Inflammation Markers and Impulsivity and Aggression in Schizophrenia Patients Involved and Not Involved in Crime

Abstract: Aim: The aim of this study was to examine the relationship between peripheral inflammatory markers and aggression and impulsivity in schizophrenia patients with and without criminal histories. Materials and Methods: The study was conducted with patients with schizophrenia involved in crimes and hospitalized in the Forensic Psychiatry ward of Elazığ Fethi Sekin City Hospital and patients with schizophrenia not involved in crimes and hospitalized in the psychiatry ward of Elazığ Mental Health and Diseases Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In a recent study involving 686 adults with bipolar disorder (vs. 343 healthy controls), researchers found that the systemic immune-inflammatory index (a combined measurement of neutrophils, lymphocytes, and platelet counts) was higher among people with bipolar disorder who had committed criminal offenses [187]. Similar findings of increased inflammatory immune markers have been reported for adults with schizophrenia who had committed crimes vs. noncriminal patients [188]. Dietary factors (omega-3 fatty acids, for example) can act as signaling molecules throughout the immune system, limiting systemic low-grade inflammation [189,190].…”
Section: Microbiome and Mechanismsmentioning
confidence: 53%
“…In a recent study involving 686 adults with bipolar disorder (vs. 343 healthy controls), researchers found that the systemic immune-inflammatory index (a combined measurement of neutrophils, lymphocytes, and platelet counts) was higher among people with bipolar disorder who had committed criminal offenses [187]. Similar findings of increased inflammatory immune markers have been reported for adults with schizophrenia who had committed crimes vs. noncriminal patients [188]. Dietary factors (omega-3 fatty acids, for example) can act as signaling molecules throughout the immune system, limiting systemic low-grade inflammation [189,190].…”
Section: Microbiome and Mechanismsmentioning
confidence: 53%